1973
DOI: 10.1139/z73-002
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of thermoregulation in the pika, Ochotona princeps

Abstract: 1973. Physiology of thermoregulation in the pika, Ochotona princeps. Can. J . Zool. 51: 11-16.The mean body temperature of pika measured by radiotelemetry under field and laboratory conditions was 40.1°C (range = 37.942.7) over an ambient temperature range of -9.3 to 24°C. The maximum daily fluctuation in any one individual was less than 2.6"C and no seasonal difference in the level of body temperature maintained was observed. Hypcrthermia and death occurred after a 2-h exposure to ambient temperatures higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
4
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 9 publications
5
85
4
1
Order By: Relevance
“…Data from our present study indicate that plateau pikas showed no winter reduction in their body mass, which is consistent with the previous Wndings (Wang and Wang 1990and Wang , 1996. It is interesting that the American pikas (Ochotona princeps), which remained active in winter, also showed no seasonal changes in body mass (MacArthur et al 1973), though the ecology of the two pika species is diVerent. American pikas inhabit areas which are covered by snow in winter and they can feed on stored food under the snow cover (Wunder 1992).…”
Section: Seasonal Variations In Body Mass and Body Fat Masssupporting
confidence: 92%
“…Data from our present study indicate that plateau pikas showed no winter reduction in their body mass, which is consistent with the previous Wndings (Wang and Wang 1990and Wang , 1996. It is interesting that the American pikas (Ochotona princeps), which remained active in winter, also showed no seasonal changes in body mass (MacArthur et al 1973), though the ecology of the two pika species is diVerent. American pikas inhabit areas which are covered by snow in winter and they can feed on stored food under the snow cover (Wunder 1992).…”
Section: Seasonal Variations In Body Mass and Body Fat Masssupporting
confidence: 92%
“…The instantaneous difference between the surface and subsurface environment routinely exceeded 20 C°at some sites. Pikas maintain a high resting body temperature ( x = 40.1°C) and a relatively low upper lethal temperature (x = 43.1°C; [30,84]). Endothermic animals compensate for ambient temperatures that exceed their upper critical temperature (UCT) by increasing metabolism [85], or by taking advantage of convective/conductive heat loss.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is possible to compare closely related species in environments that differ markedly in the amount of oxygen available but are comparable in other environmental parameters (Table 1). Pikas are extremely active foragers year-round and have high metabolic rates (MacArthur and Wang, 1973) with no form of metabolic reduction such as daily torpor, aestivation or hibernation (Krear, 1965;MacArthur and Wang, 1973). Thus, their demand for a high rate of ATP turnover is not decreased by metabolic reduction strategies.…”
mentioning
confidence: 99%